Minimisation of Construction Waste Using the Principles of Waste Management - Ting, Sim Nee; Sakawi, A. M. F.; Lau, Hieng Ho; Whyte, A. (Academy of Sciences Malaysia., 2022)
Construction industry being largest consumer of raw materials derived from natural resources also produces high amount of material waste that negatively impacts the environment . The building industry alone in Malaysia has reportedly generated approximately 25,600 tonnes of construction and demolition wastes daily due to rapid development. Therefore, any means of reducing material waste will not only result in significant cost savings within the projects but also reducing the pressure on the landfills and ease environmental concerns dealing with such waste conversion and recycling; and reduction. This study examines the causes and prevention of material waste in the construction specifically the building industry through the principles of waste management available. Questionnaires survey is the main tool deployed for data collection. The average and relative index were used to analyse the various aspects of the data collected. Stages of works used for the study include the material handling and storage stage; procurement of material stage; usage and operation of the material stage; and the design and documentation stage. The results indicate that respondents are aware of the concept of waste management but lack of awareness on the availability of such guidelines. It is hopeful that this study can improve on waste management implementation in order to uptake the principle of reduce, recycle and reuse material waste so as to reduce construction costs, provide good savings to the end users and improve the level of productivity of the nation.